Jie-Yu Pill, A Proprietary Herbal Medicine, Ameliorates Mood Disorder-Like Behavior and Cognitive Impairment in Estrogen-Deprived Mice Exposed to Chronic Unpredictable Mild Stress: Implication for a Potential Therapy of Menopause Syndrome - Zhou, Xi-Dan; Yang, Xin-Jing; Zheng, Yu; Qin, Zong-Shi; Sha, Wei; Chen, Gang; Zhang, Zhang-Jin (Frontiers in Psychiatry, 2020)
Jie-Yu Pill (JYP) is a proprietary herbal medicine initially developed to treat menstrual mood disorders. This study sought to determine whether JYP could alleviate menopausal psychiatric symptoms in ovariectomized (OVX) mice, an animal model of estrogen deprivation, exposed to chronic unpredictable mild stress (CUMS) and the underlying mechanisms in comparison with estrogen therapy. The OVX+CUMS mice were treated with 0.3 mg/kg estradiol (E2), 2.5 g/kg or 5 g/kg JYP for 36 days, and tested in multiple behavioral paradigms. Serum, uterus, and brain tissues were collected for the measurement of hypothalamus-pituitary-ovarian axis (HPO) and hypothalamus-pituitary-adrenal (HPA) axis hormones, γ-aminobutyric acid (GABA), glutamate, neurotrophins, and estrogen receptors. JYP and E2 had comparable efficacy in reducing anxiety- and depression-like behavior and cognitive impairment of the OVX+CUMS mice. E2 strikingly increased ratio of uterus to body weight of the OVX+CUMS mice, but JYP did not. Both agents suppressed HPO-axis upstream hormones, inhibited HPA-axis hyperactivity by reinstating hypothalamic GABA, restored hippocampal and prefrontal glutamate contents and its receptor expression in the OVX+CUMS mice. While JYP and E2 protected against decreases in hippocampal and prefrontal neurotrophins and estrogen receptors of the OVX+CUMS mice, unlike E2, JYP had no significant effects on these biomarkers in the uterus. These results suggest that JYP has comparable efficacy in ameliorating mood disorder-like behavior and cognitive impairment induced by a combination of estrogen deprivation and chronic stress in association with certain differential uterus-brain mechanisms compared to estrogen therapy. JYP may be a potential therapy for menopause-associated psychiatric disorders.